2022
DOI: 10.3390/ijms23062957
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical-Stress-Related Epigenetic Regulation of ZIC1 Transcription Factor in the Etiology of Postmenopausal Osteoporosis

Abstract: Mechanical loading exerts a profound influence on bone density and architecture, but the exact mechanism is unknown. Our study shows that expression of the neurological transcriptional factor zinc finger of the cerebellum 1 (ZIC1) is markedly increased in trabecular bone biopsies in the lumbar spine compared with the iliac crest, skeletal sites of high and low mechanical stress, respectively. Human trabecular bone transcriptome analyses revealed a strong association between ZIC1 mRNA levels and gene transcript… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…Located on chromosome 3, ZIC1 is a known meningeal identity gene. Studies have shown that ZIC1 promoter methylation was related to the etiology of postmenopausal osteoporosis [16], and patients with RA are at high risk of osteoporosis [17–20]. Our findings suggest that ZIC1 may be associated with RA susceptibility, and deserve further in‐depth research.…”
Section: Resultsmentioning
confidence: 55%
“…Located on chromosome 3, ZIC1 is a known meningeal identity gene. Studies have shown that ZIC1 promoter methylation was related to the etiology of postmenopausal osteoporosis [16], and patients with RA are at high risk of osteoporosis [17–20]. Our findings suggest that ZIC1 may be associated with RA susceptibility, and deserve further in‐depth research.…”
Section: Resultsmentioning
confidence: 55%
“…Our skull-BMD study underscored genes with mechanosensing properties, including the novel BMD-associated gene ZIC1 , which encodes a zinc-finger transcription factor. A few studies have demonstrated mechano-function properties of ZIC1 , including its differential expression in skeletal regions of higher and lower mechanical load, also ZIC1 immunolocalization in the cytoplasm, and translocation to the nucleus of murine osteocytes upon fluid shear and stress experiments ( 111 , 112 ). While more studies are needed to evaluate ZIC1 function in osteocytes and its function as a mechanosensing gene, its current understanding corroborates the high potential of GWAS for SK-BMD to identify genes with mechanosensing properties.…”
Section: Osteoporosis Meets Craniosynostosismentioning
confidence: 99%